2017
DOI: 10.1080/14764172.2017.1342039
|View full text |Cite
|
Sign up to set email alerts
|

Brachial plexus injury after microwave-based treatment for axillary hyperhidrosis and osmidrosis

Abstract: Axillary hyperhidrosis combined with osmidrosis is a common problem, especially in Asian communities, that patients find annoying. Even though several surgical techniques have been reported to treat hyperhidrosis/osmidrosis permanently, patients would prefer a non-surgical approach. A microwave-based device was invented during this decade, and it has proven to be a safe and efficient way to treat axillary hyperhidrosis/osmidrosis without major complications. Mild complications reported are vacuum-associated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 7 publications
0
22
0
1
Order By: Relevance
“…Although the maximum energy setting was selected, the treatment did not produce severe adverse effects with high volume fluid anesthesia, to create a space between skin and nerves. Chang et al reported on a severely underweight female treated at energy level 5 who did not fully recover after 6 months . In our study, one underweight female sustained moderate altered sensation in the treatment limb and recovered within 6 months.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Although the maximum energy setting was selected, the treatment did not produce severe adverse effects with high volume fluid anesthesia, to create a space between skin and nerves. Chang et al reported on a severely underweight female treated at energy level 5 who did not fully recover after 6 months . In our study, one underweight female sustained moderate altered sensation in the treatment limb and recovered within 6 months.…”
Section: Discussionmentioning
confidence: 41%
“…In both this and another study, four of 81 subjects (4.9%) and one of 31 (3.2%) achieved full sweat reduction with one session using low energy level 1 or 3, respectively [10,11]. Two sessions are usually scheduled 3 months apart with severe PAH using a low energy level [10,11,[13][14][15][16][17][18]. In these previous studies, the percentage of responders with a 2-point drop in HDSS score were stable from 1 month (67%) to 12 months (38-55%) [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, there was improvement in the HDSS but no difference in gravimetry. Because of the non‐selective thermal component, this form of treatment may also damage other structures such as nerves .…”
Section: Treatment Of Primary Hyperhidrosismentioning
confidence: 99%
“…Klinisch zeigte sich eine Besserung des HDSS, jedoch keine Unterschiede der Gravimetrie. Auch bei dieser Therapie kann es durch die ungerichtete thermische Komponente zur Schädigung zum Beispiel von Nerven kommen .…”
Section: Therapie Der Primären Hyperhidroseunclassified